USING MYCOBACTERIOPHAGES IN TREATMENT OF TUBERCULOSIS - Бичков О. І.; Ляшенко О. О.; Потейко П. І.; Константиновська О. С.; Галайченко О. М. (World of Medicine and Biology, 2015)
Using viruses as treatment of infectious diseases has wide experience, and it is potential alternative (or at least an additional supplement)to antibiotic therapy. Considering the experience of the phage treatment of bacterial infections, including and non-tuberculous mycobacterial disease, we suggest possibility of development of viral-based treatment for tuberculosis with M. tuberculosis-virulent bacteriophages. Mycobacteriophagesare usedin scientific practice, as model organisms for study of divergence of morphological features and structure of genome during viral evolution, as well as to study the phenomenon of viral lysogeny. It is expected, that phage treatment will significantly reduce morbidity and mortality because of tuberculosis, especially in severe cases or for patients with poor tolerance of standard treatment of tuberculosis, and may help to avoid complications associated with chronic tuberculosis infection. The significant advantage of bacteriophage treatment is possibilityof managing children and pregnant women. In addition to the experience of using bacteriophages in tuberculosis and other septic and infectious diseases, the article describes examples of viruses infecting of Mycobacterium (D29, L5, TM4, Bo4, DS6A, Bxb1), which havean experimental confirmation of infections of mycobacteria, including M. tuberculosis. This article briefly describes an applicability of these viruses for diagnostic purposes, which are to determine drug resistance of M. tuberculosis. It is assumed that lysogenic phages can be used as a tool for specific prophylaxisby creating a recombinant BCG vaccine. Furthermore, the article considers capabilities of these viruses, for designing polyphagic drug with high efficacy that can avoid possible emergence of resistant strains. Among the notable features are the ability of Bxb1 to insert its genes into the mycobacterial genome site,which is responsible for the mycolate synthesis, and a possibility of DS6A to infect all species of tuberculosis complex (M. tuberculosis, M. bovis, M. africanum). ТМ4 иD29 have been tested in an experiments of delivering them into macrophages with liposomal capsules. Potential problems, that can arise while using viral drugs (which includes mutagenic effect, difficulties at the stage of delivery to the site of infection, an immune response of the organism to phages), and suggestions of some possible ways to eliminate them, are revealed in the end of an article.